Sawflies of the genus Emphytopsis (Hymenoptera, Tenthredinidae) associated with Stewartia (Theaceae) in Japan - Shinohara, Akihiko; Saito, Takeshi; Ibuki, Shin-Ichi; Ibuki, Shin-Ichi; Hara, Hideho (Zootaxa, 2014)
Japanese species of the sawfly genus Emphytopsis Wei & Nie, 1998, are reviewed and the following four species are recognized and keyed: E. flatoserrula Wei, 2011, from Kyushu, E. nigromaculata (Takeuchi, 1952) from Honshu, Shikoku and Kyushu, E. shinoharai Wei & Niu, 2011, from Honshu and Shikoku, and E. vernalis Shinohara, n. sp., from Honshu and Kyushu. Stewartia pseudocamellia Maxim. (Theaceae) is recorded as a host plant for E. nigromaculata and E. vernalis and the larvae of these two species are briefly described. The life history of these two species is discussed based on field observations and rearing records.